Mapping Visualization Analysis of Computer Science Research data in 2017-2021 on the Google Scholar database with VOSviewer - Al Husaeni, Dwi Fitria; Nandiyanto, Asep Bayu Dani (Universitas Komputer Indonesia, 2022)
The purpose of this research is to examine the development and interrelationships between terms in computer science research using mapping analysis with VOSviewer. The research data was collected from the Google Scholar database for the period 2017-2021 using the Publish or Perish 7 application. Data collection was based on the keyword